The Financial Literacy of Women Owners of Small and Medium Scale Enterprises in Sri Lanka - Anuradha, P A N S (The journal of contemporary issues in business and government, 2021)
The success of the small and medium-sized enterprises depends extensively on the owner’s ability to be financially literate in managing finance-related matters of the business, irrespective of his or her gender. The purpose of this study is to identify the level of financial literacy of the women owners of small and medium sized enterprises in Sri Lanka. The construct ‘financial literacy’ was measured based on five dimensions, which are finance related awareness, financial planning, bookkeeping and accounting, knowledge about business terminology, risk management, and diversification. The convenience sampling method was applied to select 242 women owners from the population involved in Women Entrepreneurs Finance Initiative in Sri Lanka. Data was collection was conducted using a structured questionnaire, complemented by over-the-telephone and personnel interviews, to assess the level of financial literacy among the women owners of small and medium-sized enterprises in Sri Lanka. Descriptive analyses were used for the data analysis, at the end of which the study identified a moderate level financial literacy among the women owners of small and medium-sized enterprises in Sri Lanka. From the five dimensions chosen, the knowledge on bookkeeping and accounting, risk management, and diversification are the aspects that women entrepreneurs need to become experts in for the success of small and medium-sized enterprises. As the pioneer study that examines the level of financial literacy of women owners of small and medium-sized enterprises in Sri Lanka, this study would provide a significant benchmark for further research in the field. Nevertheless, the study also highlights the importance of including financial literacy education both for primary and tertiary educational institutions.